Chrześcijaństwo a kultury w Ameryce Łacińskiej - Pietrzak, Andrzej (Studia Nauk Teologicznych PAN, 2020)
The purpose of the article is to systematize the main issues related to the encounter of Christianity with Latin American cultures. The study is based on both Latin American theological publications and various documents of the Roman Catholic Church. In the first part the problem of Christianity’s encounter with cultures of this region from historic perspective is discussed by pointing out to its negative, ambiguous and positive aspects. The second part is devoted to classification of culture circles, significant from the point of view of evangelization and inculturation (cultures of urban agglomeration, rural regions, Indian and Afro-Latin American cultures, poverty, elites, cyber culture and popular culture). In the final section we paid attention to the issue of up-coming culture and its trends (modernism and postmodernism, secularism, socio-political ideologies, the role of mass media, the tensions between globalization process and appreciation of local traditions).